The Potential of Using the New Species Monarda Didyma L. for Introduction in Western Siberia - Kriklivaya , Aastasia; Shorin, Nikolay (KnE Life Sciences, 2021)
This article examines the introduction and use of the new species Monarda didyma L. in the conditions of Western Siberia. The rhythm of the seasonal development of the longrhizome-taprhizome life form was investigated. The timing and duration of the basic phenological phases were determined and their temperature thresholds were identified. Based on the phenological development, it was established that M. didyma can be classified as a long-growing evergreen plant. According to the identified blossoming period, the species falls into the long-flowering late-summer group. The presented phenological spectrum represents an important comparative and practical tool for Western Siberia and other geographical areas. The new species has a promising outlook for cultivation in Western Siberia and possesses a high adaptive potential, which allows for its use as an essential-oil-bearing, aromatic, decorative and melliferous plant. Keywords: M. didyma, of using, introduction, rhythm of seasonal development